Battery Health Diagnosis Approach Integrating Physics‐Based Modeling with Electrochemical Impedance Spectroscopy. Issue 4 (23rd February 2022) - Galatro, Daniela; Da Silva, Carlos; Romero, David A.; Gong, Zhe; Trescases, Olivier; Amon, Cristina H.
Abstract : Herein, a battery health diagnosis approach that combines electrochemical performance aging and lumped thermal models with electrochemical impedance spectroscopy and voltage monitoring is proposed, allowing the segregation and quantification of ohmic, chemical, and diffusion‐mechanical related losses. This approach accurately identifies battery lifetime thresholds such as first‐life, second‐life, and turnaround points, by combining the use of a capacity indicator and overpotentials as battery health indicators. This approach, which is demonstrated at the cell level, is scalable to module and pack levels and applicable to different cell chemistries and battery configurations. This battery health diagnosis approach is validated with performance and degradation data from lithium iron phosphate and nickel–manganese–cobalt cells, showing good agreement when comparing the predicted capacity fade against measured values. Abstract : Herein, a battery health diagnosis approach that combines electrochemical performance aging and lumped thermal models with electrochemical impedance spectroscopy and voltage monitoring is proposed, allowing the segregation and quantification of ohmic, chemical, and diffusion‐mechanical‐related losses. This approach accurately identifies battery lifetime thresholds combining the use of a capacity indicator and overpotentials as battery health indicators.